Inovasi Mie Kering Ubi Jalar Kuning (Ipomoea batatas L.) dengan Penambahan Ceker Ayam - Ahda Sabila; Niken Purwidiani; Ita Fatkhur Romadhoni; Nufimbar Susy Anindita Handayani (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the organoleptic quality of dry noodles made from yellow sweet potato (Ipomoea batatas L.) with the addition of chicken feet, determine the best formulation, and identify the nutritional content of the selected product. The research method used is an experiment with several variations in the proportion of chicken feet addition. Sensory quality assessment was carried out using a hedonic scale sensory test sheet instrument that includes attributes of color, shape, aroma, taste, elasticity, and overall preference, involving semi-trained panelists. Sensory test data were analyzed using analysis of variance (ANOVA) and continued with Duncan's test to determine differences between treatments. The results showed that the addition of chicken feet affected the organoleptic quality of dry noodles, with the panelists' acceptance level being in the category of slightly liking to liking. The best formulation was obtained with the addition of 30% chicken feet which produced a bright yellow color, relatively uniform noodle shape, balanced aroma and taste, and a chewy and non-breakable texture. A proximate analysis of the best formulation revealed a carbohydrate content of 70.45%, protein 14.26%, fat 3.96%, ash 1.78%, and moisture 9.55%. These results demonstrate the potential for developing locally sourced dry noodles with good nutritional value and acceptability.